(untitled) (Journal of Nepal Geological Society, 2022)
Large-scale landslides (LSL) are characterized by complex nature of failure mechanism, which depend on geological setting and associated factors of the area. The aim of this research is to identify the distribution pattern of LSL and all landslides in the central Nepal Himalaya and evaluation of their controlling factors. 7239 landslides were extracted from the study area by the interpretation of satellite imageries and field surveyed information. 28 landslides were classified as LSL and descriptive statistics were calculated. A comparative susceptibility assessment between all landslides and LSL was performed by frequency ratio model (FRM). Landslide susceptibility assessed from FRM was classified into five categories using the natural breaks method and adjustment from field evidences: very low, low, medium, high, and very high. The very high, high and medium susceptibility classes comprised of 38.91%, 33.29%, 18.76% for all landslides, and 39.51%, 29.65%, 20.98% for LSL. The result clearly indicated that the role of controlling factors varies differently depending upon the size of distributed landslides. To understand the significance of controlling factors for LSL, different potential cases were validated by success rates with area under the curve (AUC). The computed AUC in success rates for LSL is 65% and for overall landslides with similar controlling factors is 75%. The AUC values in different potential cases showed that the prime factors to control the LSL are geomorphology, rainfall, and geological structures.